2017
DOI: 10.1142/s021830131750077x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion dynamics of 30Si +238U reaction using variety of interaction potentials

Abstract: The fusion dynamics of [Formula: see text] reaction has been studied using different theoretical approaches like energy-dependent Woods–Saxon potential (EDWSP) model, coupled channel formulation and Wong approach. At sub-barrier energies, the anomalously large enhancement of the fusion cross-section signifies the importance of barrier modification effects for the adequate addressal of experimental data. The EDWSP model, wherein barrier modification effects are introduced via the energy-dependent diffuseness pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 38 publications
6
30
0
Order By: Relevance
“…tion. As a consequence, an enhancement is observed in the fusion probability of heavy/superheavy nuclear systems, with the inclusion of -deformed nuclei as the target, projectile, or both the colliding partners [13][14][15][16][17][18][19][20][21]. In addition, the relevance of higher-order deformations (with axial-and reflection-symmetries) is also analyzed in reference to the fusion barrier characteristics [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…tion. As a consequence, an enhancement is observed in the fusion probability of heavy/superheavy nuclear systems, with the inclusion of -deformed nuclei as the target, projectile, or both the colliding partners [13][14][15][16][17][18][19][20][21]. In addition, the relevance of higher-order deformations (with axial-and reflection-symmetries) is also analyzed in reference to the fusion barrier characteristics [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exploration of octupole deformed nuclei is important for extracting the appropriate nuclear structure because significant enhancements can be found in electric dipole moments (EDMs) [27]. Also, in the nuclear fusion process, it has been observed that [35] the nonzero EDMs in one of the fusion partners ( 16 O+ 144 Ba and 224 Ra) may have a significant impact on the fusion barrier and corresponding cross-sections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations